Expanding “Pawonningvian” MSME Market Reach Utilizing Google Business Profile Use in Gunung Anyar Village - Prameswari, Nur Shadrina; Wikartika, Ira (Institut Teknologi Nasional, Bandung, 2024)
This community service program is dedicated to boost the marketing and reach of Micro, Small, and Medium Enterprises (MSMEs), particularly in Gunung Anyar Village, using digital technology, especially the Google Business Profile platform. MSMEs are vital for economic stability and demonstrated resilience during the early 2020 Corona pandemic, which saw a significant shift to digital trade and marketing. However, MSMEs in Gunung Anyar Village encountered challenges in embracing digital marketing. Therefore, utilizing Google Business Profile is considered a practical solution. It offers MSMEs a platform to visually display their locations on Local Search Engine and Google Maps, featuring a user-friendly interface for both tech and non-tech users. The goal is to enable MSMEs in Gunung Anyar Village to broaden their market presence, making it easier for people to discover and connect with them on Local Search Engine and Google Maps, ultimately fostering increased sales and sustainability in the digital era. This initiative is anticipated to positively impact the growth of local MSMEs and the overall economy.